Multiyear Baleen Endocrine Profiles Suggest a Longer Estimated Gestation in Southern Right Whales (Eubalaena australis) - Loraine Shuttleworth; Andre Ganswindt; Kathleen E. Hunt; Alejandro Fernández Ajó; Estefan Pieterse; S. Mduduzi Seakamela; Chantel Schoeman; Els Vermeulen (Ecology and Evolution)
ABSTRACT Gestation length is a key reproductive parameter influencing fecundity, population growth rates, and the recovery potential of baleen whales. However, direct knowledge of the gestation length in these large mammals remains limited, primarily inferred from whaling and observational data. Over the past decade, southern right whales have experienced a decline in reproductive success, likely linked to climate‐change‐induced shifts in foraging conditions. Understanding the population‐level consequences of these changes requires detailed longitudinal reproductive data. This study analyzes multiyear steroid hormone profiles in the baleen of adult female southern right whales stranded along the South African coast. Results show an extended hormonal pattern characterized by two peaks in progestogens between 20 and 25 months—suggesting putative pregnancies lasting substantially longer than previous estimates. Sharp estrogen peaks during periods of elevated progestogen phases may indicate hormonal regulation of myometrial contractions at birth. A positive correlation between progestogens and glucocorticoids suggests a role for glucocorticoids in pregnancy maintenance, while androgens provide limited insight into female reproduction in this species. These findings imply a longer‐than‐expected gestation period for southern right whales and potentially across the balaenid family. This has important implications for understanding the timing and location of conception, relevant for conservation management strategies. Multipopulation studies alongside individual sighting histories are recommended to refine our understanding of southern right whale reproduction further.